Living Together in the Company: Operational Efficiency as a Function of Social and Relational Dynamics in Organizations - Sartori, Riccardo; Tommasi, Francesco; Ceschi, Andrea; Zene, Mattia; Morandini, Sofia; Monti, Michele; Gostimir, Marija (Italian Sociological Review, 2023)
As Gozzoli (2016) points out, living together in the company has always been a complex challenge, since in organizations people find themselves interacting, developing relationships, producing, and share spaces and time, with little chance to choose each other, a phenomenon known as organizational coexistence. And yet people in the company are asked to cooperate to achieve the organizational goals, that is to say, goals set by the company, not by workers and employees. The article is a critical review that deals with the concepts of operational efficiency (good job performance) and interactive efficiency (good organizational climate) in the perspective of organizational coexistence, and reaffirms the concept expressed by Bass (1960) that without interactive efficiency, operational efficiency is less likely to be achieved.